2011
DOI: 10.1128/aac.00306-11
|View full text |Cite
|
Sign up to set email alerts
|

Commonality among Fluoroquinolone-Resistant Sequence Type ST131 Extraintestinal Escherichia coli Isolates from Humans and Companion Animals in Australia

Abstract: Escherichia coli sequence type 131 (ST131), an emergent multidrug-resistant extraintestinal pathogen, has spread epidemically among humans and was recently isolated from companion animals. To assess for humancompanion animal commonality among ST131 isolates, 214 fluoroquinolone-resistant extraintestinal E. coli isolates (205 from humans, 9 from companion animals) from diagnostic laboratories in Australia, provisionally identified as ST131 by PCR, selectively underwent PCR-based O typing and bla CTX-M-15 detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 48 publications
(50 reference statements)
3
91
2
Order By: Relevance
“…Companion animals live in close proximity to humans and receive medical treatment more frequently than food-producing animals [23]. Platell et al reported that some fluoroquinolone-resistant Escherichia coli isolates that were derived from companion animals (i.e., dogs and cats) were very similar to the ones found in humans [27].…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Companion animals live in close proximity to humans and receive medical treatment more frequently than food-producing animals [23]. Platell et al reported that some fluoroquinolone-resistant Escherichia coli isolates that were derived from companion animals (i.e., dogs and cats) were very similar to the ones found in humans [27].…”
mentioning
confidence: 90%
“…DNA amplification and sequencing of QRDRs and PMQR: Mutations in the QRDRs of the gyrA, parC, parE and gyrB genes were detected by direct DNA sequencing of their PCR products, as described in previous studies [27,31]. Nucleotide sequences were determined using a BigDye Terminator v3.1 Cycle Sequencing Kit with a 3130 Genetic Analyzer (Applied Biosystems, Foster City, CA, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ST131-B2 strains are of major concern on the global stage as a clonal group that is both virulent and drug-resistant, and capable of causing extraintestinal disease in both humans and animals (Platell et al, 2011a). A single fluoroquinolone-susceptible ST131-B2 isolate was identified, which possessed a comparatively high virulence gene score of eight.…”
Section: Discussionmentioning
confidence: 99%
“…One concerning trend documented in recent years has been the increased prevalence of nonsusceptibility to antimicrobials observed in canine urinary tract isolates, in particular to fluoroquinolones, third generation cephalosporins, and clavulanic acid-potentiated β-lactams (Cooke et al, 2002;Mazzuli, 2002;Ball et al, 2008;Sidjabat et al, 2009;Platell et al, 2011a;Hall et al, 2013;Wagner et al, 2014;Chang et al, 2015;Rzewuska et al, 2015). The availability of many of these drugs in oral forms that reach high concentrations in the urine following absorption, along with their efficacy against Gram-negative pathogens in particular, has resulted in their widespread use in companion animals.…”
Section: Observations Of Increasing Antimicrobial Resistance In Caninmentioning
confidence: 99%